Pengaruh philanthrophy disclosure terhadap nilai perusahaan dengan profitabilitas sebagai variabel moderasi - Siti Narsiah (Faculty of Economics and Business Mulawarman University, 2016)
The aims of this research are to know : (1) The influence of philanthropy disclosure to firm value (2) The Influence of profitability to firm value and (3) The influence of Profitability as the moderating variable in relations between philanthropy disclosure and firm value. This research sample is philanthropy disclosure on all companies registered in Indonesian Stock Excange(IDX) in 2014 by using method of purposive sampling. There are 61 companies in 2014 which fulfilling criterion as this research sample. The analysis method of this research is Multiple Regression Analysis and Moderating Regression Analysis. The result of research show that the effect of philanthropy disclosure to firm value was no significant. While the effect profitability to firm value was positive significant. And profitability is can strengthen relation between philanthrophy disclosure and firm value.Keyword: Philanthrophy Disclosure, Profitability, Firm Value